A novel locus on mouse chromosome 7 that influences survival after infection with tick-borne encephalitis virus - Palus, Martin; Sohrabi, Yahya; Broman, Karl W; Strnad, Hynek; Šíma, Matyáš; Růžek, Daniel; Volkova, Valeriya; Slapničková, Martina; Vojtíšková, Jarmila; Mrázková, Lucie; Salát, Jiří; Lipoldová, Marie (BMC neuroscience, 2018)
BACKGROUND: Tick-borne encephalitis (TBE) is the main tick-borne viral infection in Eurasia. Its manifestations range from inapparent infections and fevers with complete recovery to debilitating or fatal encephalitis. The basis of this heterogeneity is largely unknown, but part of this variation is likely due to host genetic. We have previously found that BALB/c mice exhibit intermediate susceptibility to the infection of TBE virus (TBEV), STS mice are highly resistant, whereas the recombinant congenic strain CcS-11, carrying 12.5% of the STS genome on the background of the BALB/c genome is even more susceptible than BALB/c. Importantly, mouse orthologs of human TBE controlling genes Oas1b, Cd209, Tlr3, Ccr5, Ifnl3 and Il10, are in CcS-11 localized on segments derived from the strain BALB/c, so they are identical in BALB/c and CcS-11. As they cannot be responsible for the phenotypic difference of the two strains, we searched for the responsible STS-derived gene-locus. Of course the STS-derived genes in CcS-11 may operate through regulating or epigenetically modifying these non-polymorphic genes of BALB/c origin. METHODS: To determine the location of the STS genes responsible for susceptibility of CcS-11, we analyzed survival of TBEV-infected F2 hybrids between BALB/c and CcS-11. CcS-11 carries STS-derived segments on eight chromosomes. These were genotyped in the F2 hybrid mice and their linkage with survival was tested by binary trait interval mapping. We have sequenced genomes of BALB/c and STS using next generation sequencing and performed bioinformatics analysis of the chromosomal segment exhibiting linkage with TBEV survival. RESULTS: Linkage analysis revealed a novel suggestive survival-controlling locus on chromosome 7 linked to marker D7Nds5 (44.2 Mb). Analysis of this locus for polymorphisms between BALB/c and STS that change RNA stability and genes' functions led to detection of 9 potential candidate genes: Cd33, Klk1b22, Siglece, Klk1b16, Fut2, Grwd1, Abcc6, Otog, and Mkrn3. One of them, Cd33, carried a nonsense mutation in the STS strain. CONCLUSIONS: The robust genetic system of recombinant congenic strains of mice enabled detection of a novel suggestive locus on chromosome 7. This locus contains 9 candidate genes, which will be focus of future studies not only in mice but also in humans.
Keywords: Carrier Proteins; mapování chromozomů; Virus Diseases; lidé; ABC transportéry; transportní proteiny; Tick-borne encephalitis virus (TBEV); Chromosomes, Human, Pair 7; Female; virové nemoci; ATP-Binding Cassette Transporters; Chromosome 7; myši; lidské chromozomy, pár 7; Humans; Genotype; Mice; viry klíšťové encefalitidy; zvířata; Mouse model; ženské pohlaví; Chromosome Mapping; Encephalitis Viruses, Tick-Borne; Animals; genotyp; Survival; Susceptibility locus; Candidate gene